2009
DOI: 10.1002/pola.23253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and rheology of biodegradable poly(glycolic acid) prepared by melt ring‐opening polymerization of glycolide

Abstract: Ring-opening polymerization (ROP) of glycolide was studied in melt conditions and in the presence of two different initiators: 1-dodecanol and 1,4-butanediol and tin(II) 2-ethylhexanoate as catalyst. Its subsequent polymerization provided poly (glycolic acid) with controlled molar masses ranging from 2000 to 42,000 g/mol with well-defined structures characterized by NMR. Their thermal properties were evaluated by DSC analysis, and a glass transition temperature at infinite molar mass (T g1 ) of 44.8 C was thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 36 publications
(60 reference statements)
4
35
0
Order By: Relevance
“…These values are in very good agreement with literature data ranging from 220 to 228 °C for T m and being around 45 °C for T g . [17][18][19][20] This fi nding is also in good agreement with previous results for PGA from polymerizations in the presence of supercritical CO 2 . [ 3 ] Interestingly, the DSC curves of PGA samples being completely soluble in HFIP do not show a glass transition.…”
Section: Resultssupporting
confidence: 82%
“…These values are in very good agreement with literature data ranging from 220 to 228 °C for T m and being around 45 °C for T g . [17][18][19][20] This fi nding is also in good agreement with previous results for PGA from polymerizations in the presence of supercritical CO 2 . [ 3 ] Interestingly, the DSC curves of PGA samples being completely soluble in HFIP do not show a glass transition.…”
Section: Resultssupporting
confidence: 82%
“…PGA is not soluble in most of the organic solvents due to its very high crystallinity. It is only soluble in fluorous solvents up to 45 000 g/mol molecular weight …”
Section: Introductionmentioning
confidence: 99%
“…Polymer blending is of major interest because it offers the prospect of a simple route to new materials with desirable properties 12, 13. Several studies of PET–PTT blends have been reported 14–16.…”
Section: Introductionmentioning
confidence: 99%